2022
DOI: 10.1038/s41598-022-07365-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of the anterior insula during targeted helping behavior in male rats

Abstract: Empathy, the understanding of the emotional state of others, can be examined across species using the Perception Action Model, where shared affect promotes an action by “Observers” to aid a distressed “Target”. The anterior insula (AI) has garnered interest in empathic behavior due to its role integrating sensory and emotional information of self and other. In the following studies, the AI was inhibited pharmacologically and chemogenetically during targeted helping. We demonstrate the insula is active during, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…The present study also lacks an “empty” virus control group to test for CNO effects alone (Experiment 2). In a previous study, we demonstrated that the same CNO dose did not have an impact on social behavior (identical task) or impact cued meth seeking [45, 46]; and CNO injections did not alter oxytocin secretion or social behavior [41]. Finally, Experiment 1 included male subjects only and Experiment 2 was not powered to detect sex differences, but our results from Experiment 2, while preliminary, do not indicate a sex effect of PVN oxytocinergic neuron activation or inhibition on cued heroin seeking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study also lacks an “empty” virus control group to test for CNO effects alone (Experiment 2). In a previous study, we demonstrated that the same CNO dose did not have an impact on social behavior (identical task) or impact cued meth seeking [45, 46]; and CNO injections did not alter oxytocin secretion or social behavior [41]. Finally, Experiment 1 included male subjects only and Experiment 2 was not powered to detect sex differences, but our results from Experiment 2, while preliminary, do not indicate a sex effect of PVN oxytocinergic neuron activation or inhibition on cued heroin seeking.…”
Section: Discussionmentioning
confidence: 99%
“…In Experiment 2, rats participated in a social interaction task to assess the impact of DREADD-induced excitation and inhibition of PVN oxytocinergic neurons on social interaction (similar to our previously published studies [44, 45]). The social interaction task began 1 week into the abstinence period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low AI males reduced chain pull latency across acquisition, whereas low AI females did not ( Supplemental Figure 1D ). Our lab and others 48-49 use change in latency over time as a proxy for learning and mastery of a behavioral task. While it cannot be ruled out that low AI females showed reduced helping behavior compared to males, it seems less likely since no differences were seen in any of the specific timepoints evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…19 , 20 , 21 , 22 Neuroscience studies in rats have further identified emotional mirror neurons of pain in the ACC 23 and the causal contribution of InC in helping behaviors. 24 Emotional mirror neurons in rats are analogous to the mirror neuron system in primates, which explains their ability to understand observed motor actions. 25 , 26 , 27 …”
Section: Introductionmentioning
confidence: 99%